CCR4 in cutaneous T‐cell lymphoma: Therapeutic targeting of a pathogenic driver. Issue 7 (7th May 2021) - Nicolay, Jan P.; Albrecht, Jana D.; Alberti‐Violetti, Silvia; Berti, Emilio
Abstract: New treatments are needed for patients with cutaneous T‐cell lymphoma (CTCL), particularly for advanced mycosis fungoides (MF) and Sezary syndrome (SS). The immunopathology of MF and SS is complex, but recent advances in tumor microenvironment understanding have identified CCR4 as a promising therapeutic target. CCR4 is widely expressed on malignant T cells and Tregs in the skin and peripheral blood of patients with MF and SS. The interaction of CCR4 with its dominant ligands CCL17 and CCL22 plays a critical role in the development and progression of CTCL, facilitating the movement into, and accumulation of, CCR4‐expressing T cells in the skin, and recruiting CCR4‐expressing Tregs into the tumor microenvironment. Expression of CCR4 is upregulated at all stages of MF and in SS, increasing with advancing disease. Several CCR4‐targeted therapies are being evaluated, including "chemotoxins" targeting CCR4 via CCL17, CCR4‐directed chimeric antigen receptor‐modified T‐cell therapies, small‐molecule CCR4 antagonists, and anti‐CCR4 monoclonal antibodies. Only one is currently approved: mogamulizumab, a defucosylated, fully humanized, anti‐CCR4, monoclonal antibody for the treatment of relapsed/refractory MF and SS. Clinical trial da1ta confirm that mogamulizumab is an effective and well‐tolerated treatment for relapsed/refractory MF or SS, demonstrating the clinical value of targeting CCR4. Abstract : C‐C chemokine receptor 4 (CCR4) is expressed on malignant T cells in cutaneous T‐cell lymphoma (CTCL). CCR4 is also expressed on Tregs and accumulation of Tregs by tumours is a known mechanism of immune escape in CTCL and other cancers. Anti‐CCR4 therapy holds potential as an antitumour treatment both as monotherapy and in combination with other existing therapies.